2014
DOI: 10.5897/jphe2014.0620
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sleepiness, circadian preference, caffeine consumption and use of other stimulants among Thai college students

Abstract: We conducted this study to evaluate the prevalence of daytime sleepiness and evening chronotype, and to assess the extent to which both are associated with the use of caffeinated stimulants among 3,000 Thai college students. Demographic and behavioral characteristics were collected using a self-administered questionnaire. The Epworth Sleepiness Scale and the Horne and Ostberg Morningness-Eveningness Questionnaire were used to evaluate prevalence of daytime sleepiness and circadian preference. Multivariable log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
0
7
1
4
Order By: Relevance
“…Later bed- and rise times have been found to be associated with increased likelihood of caffeinated drink and fast-food consumption and a lower likelihood of dairy product consumption in a small-scale cross-sectional survey of adolescents (83). Several other studies have reported cross-sectional associations between an evening chronotype and higher consumption of stimulants such as caffeine, energy drinks, sugar-sweetened beverages, and alcohol in adolescents (24) and in college or university students (49, 78, 79, 84). In another study involving students and professionals, individuals with an evening chronotype were found to consume more alcohol, coffee, and cola, whereas morning types consumed more tea (86).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Later bed- and rise times have been found to be associated with increased likelihood of caffeinated drink and fast-food consumption and a lower likelihood of dairy product consumption in a small-scale cross-sectional survey of adolescents (83). Several other studies have reported cross-sectional associations between an evening chronotype and higher consumption of stimulants such as caffeine, energy drinks, sugar-sweetened beverages, and alcohol in adolescents (24) and in college or university students (49, 78, 79, 84). In another study involving students and professionals, individuals with an evening chronotype were found to consume more alcohol, coffee, and cola, whereas morning types consumed more tea (86).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…sensation-seeking [43][44][45], reduced harm-avoidance and persistence [44], greater general risk-taking across a number of domains including financial, ethical and recreational decision-making [46,47], substance use [48,49] increased coffee and stimulant use [50] and smoking [51]. More recently, Hwang et al [52], observed an association between eveningness and greater impulsivity in a large sample (N = 1000) of community-dwelling adults (age range 20-77 years) thereby suggesting that the association between circadian typology and impulsivity is not restricted to youth and young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…We also reported in the current study that the risk of car accidents increased significantly in subjects using frequently energy drinks. Although being potentially a counter-intuitive result, recent studies also reported that subjects who consumed energy drinks were more likely to be daytime sleepers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%